Fast glomerular quantification of whole ex vivo mouse kidneys using Magnetic Resonance Imaging at 9.4 Tesla - Chacón-Caldera, Jorge; Gretz, Norbert; Schad, Lothar R. (Zeitschrift für medizinische Physik, 2016)
A method to measure total glomerular number (Nglom) in whole mouse kidneys using MRI is presented. The method relies on efficient acquisition times. A 9.4 T preclinical MRI system with a surface cryogenic coil and a 3D gradient echo sequence were used to image nine whole ex vivo BALB/c mouse kidneys labelled with cationized-ferritin (CF). A novel method to segment the glomeruli was developed. The quantification of glomeruli was achieved by identifying and fitting the probability distribution of glomeruli thus reducing variations due to noise. For validation, Nglom of the same kidneys were also obtained using the gold standard: design-based stereology. Excellent agreement was found between the MRI and stereological measurements of Nglom, with values differing by less than 4%: (mean ± SD) MRI = 15 606±1 178; stereology = 16 273±1 523. Using a robust segmentation method and a reliable quantification method, it was possible to acquire Nglom with a scanning time of 33minutes and 20seconds. This was more than 8 times faster than previously presented MRI-based methods. Thus, an efficient approach to measure Nglom ex vivo in health and disease is provided.